Mobile drawing methods in landscape research: collaborative drawing in Kathmandu Valley, Nepal. (17th November 2022) - Fox, Alice; Macpherson, Hannah; Oli, Nischal; Ranjit, Ashmina; Thapa, Sangeeta; Aggett, Siân; Church, Andrew
Abstract: In this paper, we show how mobile drawing methodologies can bring the dynamic, relational and non-representational qualities of landscape encounters to the foreground. The research paper discusses a mobile drawing project that took place in the Kathmandu Valley, Nepal. The project entitled 'Taxi Guff-Gaff' invited participants to undertake a collaborative drawing and conversational journey. Mobile drawing together on a bumpy taxi journey required artist participants to move together and literally 'pay attention to the moment at hand'. In so doing it produced imagery that foregrounds the inherent dynamic quality of all our landscape encounters. We propose that mobile drawing offers an immersive way to relate to the urban landscape and each other and can open up spaces of landscape research that centre on speculative forms of thinking, being, drawing and conversation.